2011
DOI: 10.1176/appi.ps.62.9.1101
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems, Psychiatric Hospitalization, and Emergency Department Use Among Psychiatric Patients With Medicaid

Abstract: OBJECTIVE This study examined the prevalence of sleep problems, and their relationship with the use of inpatient and emergency department services among Medicaid psychiatric patients. METHODS Participants were 1,560 Medicaid psychiatric patients identified in a ten-state random survey of psychiatrists. Sleep problems were assessed by clinician ratings. RESULTS Over 75% of Medicaid psychiatric patients experienced a sleep problem, and in approximately 50% of patients these problems were moderate to severe. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
0
8
0
5
Order By: Relevance
“…The Kaiser Family Foundation estimates that health care costs for Americans aged 65 and older average $8,776 per person each year, with a large proportion of spending on hospitalizations, home health care services, and nursing home use (5). There is some evidence that insomnia is associated with increased use of health services in younger and in clinical populations (6)(7)(8)(9). There is also evidence extending these findings to older adults in clinical settings (eg, nursing homes, hospitals [10,11]).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Kaiser Family Foundation estimates that health care costs for Americans aged 65 and older average $8,776 per person each year, with a large proportion of spending on hospitalizations, home health care services, and nursing home use (5). There is some evidence that insomnia is associated with increased use of health services in younger and in clinical populations (6)(7)(8)(9). There is also evidence extending these findings to older adults in clinical settings (eg, nursing homes, hospitals [10,11]).…”
mentioning
confidence: 99%
“…Spira and colleagues used wrist actigraphy as an objective measure of sleep in community-dwelling older women and found that greater time awake after the onset of sleep and worse sleep efficiency were associated with a greater odds of subsequent placement in long-term care (13). However, the majority of studies have used clinical samples or did not focus on older samples (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…[14,25,26, Bir diğer çalışmada psikiyatri hastalarının %78'i psikiyatristleri tarafından uyku problemi yaşıyor olarak değerlendirilmiş, bu hastaların %36'sının uyku probleminin orta, %13'ünün şiddetli olduğu ifade edilmiştir. [34] Bu çalışmada ise, araştırma grubunun %67.8'inin uyku kalitesi kötü olarak tespit edilmiştir. Araştırmamızda toplam PUKİ ortalama puanı 8.1 olarak elde edilmiş olup, hastaların kötü uyku kalitesine sahip oldukları görülmektedir.…”
Section: Discussionunclassified
“…Çeşitli çalışmalarda da benzer sonuçların bildirildiği görülmektedir. [21,30,34] Ancak erkekler arasında uyku kalitesinin daha kötü olduğunu bildiren [25,37] çalışmaların yanı sıra erkeklerle kadınlar arasında uyku kalitesi açısından fark bulunmadığını rapor eden çalışmalara da rastlanmaktadır. [3,31] Yaş ilerledikçe gece uyanık kalma zamanı ve kronik hastalık gelişme riski artmakta olup, bireyin uyku kalitesinin kötüleşmesi beklenen bir durumdur.…”
Section: Discussionunclassified
“…There were no sleep-related disorders documented on Axis I for this sample, which highlights the underutilization of these important diagnoses for psychiatric inpatients in this sample. Sleep disorders are associated with a greater odds of psychiatric inpatient hospitalization (107), and the co-occurrence between sleep problems, psychiatric conditions and suicide ideations is well documented (25); yet in this sample, the diagnoses were not apparent upon admission. Given this wealth of understanding, this is a surprising finding because of the robust relationship between sleep disturbance and suicide risk.…”
Section: Suicide Status Group and Admission Psychiatric Diagnoses (Hymentioning
confidence: 85%